KEKOHESIAN WACANA DAKWAH DI TELEVISI - Hartini Hartini (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2018)
This research was conducted with the general purpose of research to obtain a description of cohesion and coherence about propoganda discourse on television. The general objective is translated into the following specific objectives, namely: (1) to describe the discourse cohesion pf propoganda on television. (2) to describe the discourse coherence of propoganda on television. Data collected by the method of observation, recording, and noting. The marker of cohence between sentences that often arises is the reference and conjuncition, while the marker substitution, ellipsis, antonyms, synonyms, collacation is rarely. The marker of effective cohesion of propoganda on television discourse is the marker reference and conjunction.